Theaflavins Are Improved by the Oxidation of Catechins in Tannase Treatment During Black Tea Fermentation - Lijuan Yang; Mengxue Zhang; Heyuan Jiang; Weiwei Wang; Jigang Huang; Shuixin Ye; Yan Chen; Shuang Liu; Jiaxin Liu (Molecules)
The treatment of black tea fermentation with different exogenous tannases was investigated, and processing parameters during black tea fermentation, including fermentation time, fermentation temperature, and exoenzyme amounts, were optimized, while the consumption and transformation pathways of catechins were analyzed. The results showed that tannase from Aspergillus niger was ultimately selected as the optimal enzyme to effectively increase the content of theaflavins by promoting the hydrolysis reaction and benzoylation reaction of catechins, resulting in a greater theaflavin (TF) content of 1.41%. The optimal processing conditions were found to be a fermentation time of 3 h, a fermentation temperature of 20 °C, and 1 g of tannase for 300 g of rolled tea leaves. Processing with the exogenous tannase could provide an ideal choice for the efficient utilization of summer and autumn fresh tea leaves, and could be used to develop summer and autumn black tea and to improve the content of theaflavins. It could also be used to develop deep processing of tea products with theaflavin extracts in the future.